The Influence of Hedonic Shopping Motives and Perceived Risk Towards Impulse Buying - Regina Eka Pratiwi; Marheni Eka Saputri (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Instagram is used as a means of business promotion. Marketing through Instagram is increasingly popular among business people, this is related to Instagram users who are increasingly growing. This research aims to determine the effect of hedonic shopping motives and perceived risk on impulse buying on online shop on Instagram. The variables used in this study are the hedonic shopping motives variable (X1), the perceived risk variable (X2) and one dependent variable (Y), the impulse buying variable. The research method used is a quantitative method with descriptive and causal research types. The population in this study are consumers who have made purchases on Instagram with a sample of 100 respondents and the sampling technique used is the non-probability sampling method with the type of purposive sampling. The results of this study indicate that the hedonic shopping motives and perceived risk variables have a positive and significant effect on impulse buying on Instagram simultaneously by 30.2%, while the remaining 69.8% is influenced by other variables not examined in this study. The hedonic shopping motives variable has a positive and significant effect on impulse buying partially on Instagram, while the perceived risk variable doesn't significantly influence the impulse buying on Instagram partially.